Temporal pattern of tuberculosis cure, mortality, and treatment abandonment in Brazilian capitals - George Jó Bezerra Sousa; Thiago Santos Garces; Maria Lúcia Duarte Pereira; Thereza Maria Magalhães Moreira; Germana Maria da Silveira (Universidade de São Paulo, 2019)
Objective: to analyze the temporal pattern of tuberculosis cure, mortality, treatment abandonment in Brazilian capitals. Method: this is an ecological study whose data source was the Information System of Notifiable Diseases for Tuberculosis (Sistema de Informação de Agravos de Notificação para Tuberculose). For analysis of temporal evolution, regressions by join points were performed considering the annual percentage variation and the significance of the trend change with 95% confidence interval. Results: 542,656 cases of tuberculosis were found, with emphasis on a 3% decrease per year in the cure rate for Campo Grande (interval: −5.0 - −0.9) and a 3.5% increase for Rio de Janeiro (interval: 1.9 - 4.7). Regarding abandonment, it decreased 10.9% per year in Rio Branco (interval: −15.8 - −5.7) and increased 12.8% per year in Fortaleza (interval: 7.6 - 18.3). For mortality, a decreasing or stationary tendency was identified, with a greater decrease (7.8%) for Porto Velho (interval:−11.0 - −5.0) and a lower one (2.5%) in Porto Alegre (interval:−4.5 - −0.6). Conclusion: the rates of cure and abandonment are far from the ones recommended by the World Health Organization, showing that Brazilian capitals need interventions aimed at changing this pattern.